Determinación del ruido ambiental generado por la transitabilidad de vehículos motorizados y su impacto ambiental de la carretera Moyobamba - Ríos Gómez, Jinith (2015)
At present, the road that joins the Moyobamba district to Yantalo, until 2012 it was only affirmed and that through a project of public investment carried out their level of improvement to what basic asphalt has been increasing the serviceability of motorized vehicles throughout the day. In this sense by means of the present investigation work it was achieved to determine the noise level that generates product of the transitabilidad . in the road, for which 03 stations of monitoring were established, the first in the km 01, the second in the km 04 and the third in the km 07 regarding Moyobamba - Yantalo. Noise measurements were made on the day shift with an interval of 15 days during 04 consecutive months (from 15 May to 30 September 2015). The meast.:rement methodology was 03 consecutive shots with a 1-minute interval to 1.50 meters in height in the right margin of San Martin. The results indicates that the road presents a Moyobamba Yantalo serviceability of 86 vehicles per hour, of which 40 % are Trimoviles, a 31 per cent are linear motorcycles and a 29 per cent are vehicles for cargo and public transport. For comparison with the ECAs la id down, the station Na. 02 located in the km 4 of the oxcart Moyobamba - Yantalo, register an average noise level of 81.1 dBA, which surpasses the ECAs applied to the Zone Industrial protection/Day Shift (80 dBA). In comparison with the ECAs for Commercial Area/Day Shift (70 dBA), the 03 monitoring stations outweigh the ECAs with an ave1·age value of 76.8 dBA as well as with re~ard to the Environmental Quality Standards - ECAs applied to the Zone Residential Protection/Day Shift (60 dBA). · These levels of average noise generated by the serviceability of motorized vehicles on the road Moyobamba - Yantalo, may be causing in the population of the environment of the pedestrian way, affectations of various kinds that is the case with hearing impairment, headache, insomnia, fatigue, stress, irritability, aggressiveness, social isolation, etc. Key words: public investment, noise level.